2020
DOI: 10.1111/bph.14902
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals as modulators of gut microbiota: Role in therapy

Abstract: As our knowledge of the various roles of the gut microbiota in the maintenance of homeostasis grows and as we learn how a disrupted microbiota may contribute to disease, therapeutic strategies that target our microbial fellow‐travellers become ever more attractive. Most appealing are those interventions that seek to modify or supplement our diet through the addition of nutraceuticals. We now know that our diet, whether in the short or long term, is a major modifier of microbiota composition and function. Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 112 publications
0
15
0
Order By: Relevance
“…The diet is a critical regulator of the composition and function of the microbiota [131]. Multiple studies have focused on the effects of macronutrients (fat, carbohydrate, and protein) on the gut microbiome.…”
Section: Microbiotamentioning
confidence: 99%
“…The diet is a critical regulator of the composition and function of the microbiota [131]. Multiple studies have focused on the effects of macronutrients (fat, carbohydrate, and protein) on the gut microbiome.…”
Section: Microbiotamentioning
confidence: 99%
“…One of the possibilities to modulate the systemic inflammatory condition is to act on the composition of the GM. It has been suggested that interventions directed to modulate the bacterial species inhabiting the gastrointestinal tract through supplementation with either probiotics/prebiotics or nutraceuticals might be effective in modifying the clinical outcomes directly or indirectly mediated by changes in the inflammatory and oxidative status [ 13 , 14 ]. Referring to patients affected by renal disease, however, the majority of scientific evidence has been obtained in experimental animal models or in the advanced stages of CKD, with few data produced in the earlier stages of the disease, when the intervention might be more plausibly effective [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The administration of nutraceuticals as well as of various supplements, such as fibers, antioxidant vitamins, omega-3 fatty acids, and herbs, has been employed to improve various diseases associated with dysbiosis [ 8 ]. In a recently published paper [ 9 ], we highlighted that research into the possible role of functional foods and nutraceuticals in mitigating immune function and actively sustain gut health is still in its infancy, especially in the Romanian market.…”
Section: Introductionmentioning
confidence: 99%